Nutritional and Pharmacological Therapy Adherence in Type-2 Diabetes Patients in a Mediterranean Region - Pinto, Ezequiel; Braz, Nídia; Nascimento, Tânia; Gomes, Eurico (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
Introduction: Type 2 diabetes patients do not value nutritional therapy in the same level as they value other types of interventions. In this study, we analysed the value that T2DM patients place on nutritional and pharmacological therapy and identified perceived barriers to nutritional therapy adherence. Methods: a non-random sample of 62 patients receiving health care in a Diabetes Clinic in the municipality of Faro, in the Portuguese region of the Algarve, was interviewed with a semi-structured protocol regarding sociodemographic characteristics, lifestyle, physical activity, and dietary habits. Additional data were collected from the patient’s clinical files and by conducting anthropometric assessment using standard methods. Results: patients show a poor dietary intake, and most are overweight (36%; n=22) or obese (53%; n=33). Physical activity is considered less important than dietary intake and pharmacologic treatment (F=19.6; p<0.001). Adherence to a Mediterranean diet is high (66%; n=41), and patients with a higher adherence to the Mediterranean diet consider their diet as having an higher quality (rSpearman=0.371; p=0.032). Value placed in dietary intake as a treatment for the disease is high, but patients seem to have a trouble in complying with the recommendations and to sustain the compliance they achieved. Conclusions: Patients should be empowered to improve their self-care. Proper, tailored interventions should be developed and implemented.